Horticulture : for a greener world - Hubbard, L. Ron (Commerce, Calif. : Bridge Publications, 2012)
"In this very special story of transcendent revelations and global repercussions, track the course of L. Ron Hubbard's horticultural discoveries. Told through articles and personal notes--here is a journey of discovery bearing upon all living things and the very essence of life itself."--
"Glossary": p. 121-150.
Includes index.
Keywords: Horticulture -- Experiments; Horticulture -- Research; Plants -- Experiments